QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK PENINGKATAN KINERJA KUALITAS PRODUK INDUSTRI KECIL MAKANAN KHAS TRADISIONAL DANGKE DI KABUPATEN ENREKANG SULAWESI SELATAN QUALITY FUNCTION DEPLOYMENT (QFD) TO INCREASE SMALL INDUSTRIAL PRODUCT QUALITY PERFORMANCE OF DANGKE TRADITIONAL SPECIAL FOOD AT ENREKANG REGENCY SOUTH SULAWESI - Ridwan, Muh. (Pembangunan Pedesaan, 2006)
This research aimed at analyzing customer, product engineering competitive assessment, and operational strategy for increasing small industrial product quality performance of dangke traditional special food on the fulfillment of consumer need and desire. The research used analysis tool of Quality Function Deployment (QFD) to describe structured mechanism in deciding consumer need. QFD consisted of monitor and right control operational process. Result of the research showed that there were three attributes used for mainly consideration to consume dangke, i.e., aroma, taste, and price. Performance of the industry was satisfy enough for cow dangke and satisfy for water buffalo one. Price and package was the most critical attribute and needed to be developed and managed seriously. Economical production cost without decreasing its quality was needed to product cheaper dangke reached by consumer. The use of good and attractive package would give positive value of the product so that the consumer could pay it with higher pricewithout decreasing satisfaction value received. Smaller package of the product (economical package) would give reachable price per unit. Package with leaves needed to be modified or changed with polypropylene plastic or aluminum foil one because it could protect water transpiration, texture, and color.